Analisis Pengaruh Inflasi dan Suku Bunga terhadap Pertumbuhan Ekonomi di Indonesia - Dinda Dewi Santika; Alya Putri Aiska; Aisyah Tiara Kusuma; Gustina Masitoh; Feri Kurniawan (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Inflation is an increase in the price of goods and services widely and sustainably in a certain period of time. Inflation has a significant influence on the economic growth of country, including Indonesia. The high level of inflation can cause instability in Indonesia’s economic growth. Interest rates are expenses and payments paid banks to customers who make product purchase dan salestransactions. generally interest rates are culculated according to a certain percentage within a certain period of time. In addition, interest rates also function as one of the aspects that influence the development and economic growth in Indonesia, both for the public and investors. This study aims to analyze the effect of inflation and interest rates on economic growth in Indonesia. The method used is a literaturee study with a descriptive qualitative approach. The results showed that inflation and interest rates had a positive influence on economic growth in Indonesia. Economic growth is reflected in increasing economic capacity in producing goods and services. Therefore, inflation control and interest rates are very important in encouraging economic growth. Strategies are needed to optimize the use of domestic products and improve export tariffs and limiting certain goods imports. The negative impact of inflation on the country’s economy includes the potential to desrease he welfare of the community, especially permanent income groups, due to the increase in price of goods that are not matched by increased income. In addition, inflation can worsen income inequality, therebyreducing the purchasing power of permanent income people.